"Sorting things out together": Young adults' experiences of collaborative practices in mental health and substance use care. Issue 2 (3rd April 2017) - Ness, Ottar; Kvello, Øyvind; Borg, Marit; Semb, Randi; Davidson, Larry
ABSTRACT: Many countries have sought reforms aimed at maximizing the potential of service users to regain as much control as possible over care decisions and through the trajectory of care. There is a robust research literature suggesting that at the core of these services are collaborative relationships in which providers respect the perspectives of the persons being served and the partnerships in which they are involved. Although the significance of collaboration is established in the mental health field in this way, what it actually means to collaborate in practice, to be partners or to be mutually involved in a partnership with young adult service users, has been given less attention. In this article, the authors explore and describe the experiences of a cohort of these young adults, paying particular attention to their perspectives on collaborative practices with practitioners. Qualitative interviews were conducted with seven young adult service users age 20 to 30. Using thematic analysis, the authors identified four overarching themes that characterized their experiences of collaborating with practitioners in mental health and addiction care: (1) don't fix me or judge me, (2) someone to sort issues out with, (3) not giving up, and (4) practical help. These findings inform the development and delivery of services to maximize positive outcomes for young adult service users with cooccurring mental health and substance use problems.